Connectivity and Application of the Principle of Multiple Intelligences in the Three Domains of Learning Mathematics - Vivian Maanu; Francis Ohene Boateng; Ebenezer Appiagyei; Hatsu Edo; Klu kwasi, Theophilus (MASI Mandiri Edukasi, 2024)
The study aimed to examine how Gardner's Multiple Intelligences applied to Ghana's Senior High School's core mathematics curriculum and instruction. The Core Mathematics curriculum was the primary document reviewed for the study. The action verbs used in the objective, section teacher-learner activities section, and the evaluation section of the core mathematics syllabus were identified and grouped with respect to the multiple intelligences. The analysis revealed that the mathematics curriculum was linked to several intelligences, although some intelligence was underserved. The Senior High School Mathematics Curriculum fails to consider diverse learning styles and preferences. It should provide a diverse range of topics using various instructional techniques. However, children with different intelligences should not experience mathematics as a hindrance. A re-evaluation is necessary to address these issues.